(untitled) (Indian Journal of Arid Horticulture, 2013)
Host plant resistance is an important component for management of the melon fruit fly, Bactrocera cucurbitae (Coquillett) owing to difficulties associated with its chemical and biological control. Ridge gourd varieties/ genotypes viz., AHRG-49, Arka Sujata, AHRG-29, AHRG-36, AHRG-47, AHRG-41, S. Manjari, AHRG-31, AHRG-33, AHRG-42, AHRG-30, AHRG-57, S. Uphal, Pusa Nasdar, AHRG-35, Jaipuri Long, AHRG- 23, AHRG-56, AHRG-53, AHRG-58, AHRG-50, AHRG-28, AHRG-43, AHRG-44, AHRG-46, AHRG-48, AHRG-52, AHRG-59 and AHRG-61 were evaluated to screen out the suitable resistant/susceptible varieties/ genotypes against the fruit fly in hot arid region of Rajasthan. The results imparted that the percentage of fruit infestation and larval population per fruit on tested varieties/ genotypes of ridge gourd varied significantly. Pooled data showed that the AHRG-49, AHRG-33, AHRG-42, AHRG-30, AHRG- 23, AHRG 58, AHRG-50, AHRG-28, AHRG-43, AHRG-52 and AHRG-59 were categorized as susceptible varieties/ genotypes with fruit infestation (70.85%, 68.13%, 57.97%, 55.93%, 70.17%, 55.00%, 53.25%, 65.75%, 57.82%, 69.68% and 65.83%, respectively) and larval population per fruit (22.27, 28.92, 25.93, 22.73, 22.63, 24.28, 22.27, 23.42, 24.12, 21.97, 24.93 and 24.13, respectively). Whereas, the varieties/ genotypes AHRG-29, AHRG-57 and Pusa Nasdar had fruit infestation (17.92%, 16.22% and 18.50%, respectively) and larval population per plant (16.60, 13.45 and 14.55, respectively) and declared as resistant varieties/ genotypes to fruit fly. The AHRG-47, AHRG-31, AHRG-48 and AHRG-61 with fruit infestation (78.02%, 80.13%, 80.10% and 79.42%, respectively) were highly susceptible varieties/ genotypes to fruit fly in pooled data of both the seasons viz., 2011 and 2012. Lower values of host plant susceptibility indices based on fruit infestation (HPSI) were recorded on resistant varieties/ genotypes , AHRG-29, AHRG-57 and Pusa Nasdar (36.12%, 32.69% and 37.29%, respectively) could be used as a source of resistance for developing ridge gourd varieties/ genotypes resistant to fruit fly.